Pengaruh Kompensasi Finansial dan Kompesasi Non Finansial Terhadap Kepuasan Kerja Karyawan - Andea Debby Prameida Nugraheni (JURNAL EKOBIS DEWANTARA, 2020)
The aims of this research is to analyse factors that affect employee satisfaction. The object under study is all the professors and staff of faculty of language and art Satya Wacana Christian University. Data collection techiques use census sampling. This research uses the primary data from questionnaires for as many 33 respondents. Analysis data using linier regression analysis. Study show that variables affect employee satisfaction. Linier regression analysis indicates each variable has a different influence. Financial compensation variable has a positive effect on job satisfaction, while non-financial compensation variable not significant effect on job satisfaction. Keywords : Financial Compensation, Job Satisfaction, Non Financial Compensation,